Online System for Gait Parameters Estimation Using a LRF Sensor for Assistive Devices (2021)
Recent implementations of sensory systems have addressed gait characterization in several assistive, rehabilitation and human-robot interaction scenarios. Sensors such as laser rangefinders, force platforms and motion tracking systems have been widely used to achieve legs’ position tracking, as well as to estimate gait spatio-temporal parameters. However, the validation of those measurements with a gold standard system is still lacking. In this sense, this work is aimed at proposing an online system for the estimation of gait parameters for walker-assisted gait with smart or robotic devices. Moreover, a validation study with an optoelectronic system was carried out. A group of 30 healthy volunteers was recruited. The trials were performed on a treadmill, where the subjects were asked to walk at 4 different speeds. The proposed system is equipped with a laser rangefinder to calculate the users’ legs position. Additionally, two adaptive filters, as well as a linear mathematical model were used to adjust the estimations of the users’ gait parameters. Results show that our proposed system is able to estimate the stride cadence and the step length with an error lower than 5% compared with the gold standard system.